KONSTRUKSI PERLINDUNGAN HUKUM DEBITUR DALAM PENYELESAIAN KREDIT BERMASALAH DENGAN PELAKSANAAN LELANG JAMINAN HAK TANGGUNGAN - Sulastri, Lusia (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2015)
Settlement of non-performing loans by auction guarantee Encumbrance often bring up the resistance of the debtor in the form of Civil Lawsuit filed to the District Court which is due to the complexity of the auction and there are some weaknesses in the Act Mortgage particular Article 6 and Article 20 is often used as an opportunity to apply for resistance by the debtor. Which is the subject of research is related to the cause of the resistance of the debtor and construct legal protection for the debtor, which will then be analyzed reasons debtor resistance and constructing legal protection for debtors. It is important for creditors to be careful in the credit granting process and the handling of non-performing loans with the auction encumbrance to keep attention on merit, good faith and respect for the property of others, the presence of assessors public good repute be important in determining the value of the limit the object of the auction.